A Bibliometric Analysis of Graph Labeling Study Using VOSviewer - Kuan, Yoong Kooi; Azahri, Khairul Azri; Rijal, Muhammad Wirawan Nabil Budiman; Mazlan, Muhammad Imran (Universitas Komputer Indonesia, 2023)
Graph labeling is a well-known theme of graph theory that involves an assignment of integers to the domain elements such as vertices or edges, or both, subject to certain conditions. A bibliometric and descriptive quantitative approach is used in this study to conduct a bibliometric analysis on graph labeling by integrating mapping analysis with VOSviewer software. The data was obtained from a Google Scholar search using the keyword